A tandem CCCH type zinc finger protein gene CpC3H3 from Chimonanthus praecox promotes flowering and enhances drought tolerance in Arabidopsis - Huamin Liu; Shiqi Xiao; Shunzhao Sui; Renwei Huang; Xia Wang; Huafeng Wu; Xia Liu (BMC Plant Biology, 2022)
Abstract Background CCCH-type zinc finger proteins play important roles in plant development and biotic/abiotic stress responses. Wintersweet (Chimonanthus praecox) is a popular ornamental plant with strong resistance to various stresses, which is a good material for exploring gene resource for stress response. In this study, we isolated a CCCH type zinc finger protein gene CpC3H3 (MZ964860) from flower of wintersweet and performed functional analysis with a purpose of identifying gene resource for floral transition and stress tolerance. Results CpC3H3 was predicted a CCCH type zinc finger protein gene encoding a protein containing 446 amino acids with five conserved C-X8-C-X5-C-X3-H motifs. CpC3H3 was localized in the cell membrane but with a nuclear export signal at the N-terminal. Transcripts of CpC3H3 were significantly accumulated in flower buds at floral meristem formation stage, and were induced by polyethylene glycol. Overexpression of CpC3H3 promoted flowering, and enhanced drought tolerance in transgenic A. thaliana. CpC3H3 overexpression affects the expression level of genes involved in flower inducement and stress responses. Further comparative studies on physiological indices showed the contents of proline and soluble sugar, activity of peroxidase and the rates of electrolyte leakage were significantly increased and the content of malondialdehyde and osmotic potential was significantly reduced in transgenic A. thaliana under PEG stress. Conclusion Overall, CpC3H3 plays a role in flowering inducement and drought tolerance in transgenic A. thaliana. The CpC3H3 gene has the potential to be used to promote flowering and enhance drought tolerance in plants.